Transcranial direct current stimulation in semantic variant of primary progressive aphasia: a state-of-the-art review - Norata, Davide; Motolese, Francesco; Magliozzi, Alessandro; Pilato, Fabio; Di Lazzaro, Vincenzo; Luzzi, Simona; Capone, Fioravante (Frontiers in Human Neuroscience, 2023)
The semantic variant of Primary Progressive Aphasia (svPPA), known also as “Semantic Dementia (SD)”, is a neurodegenerative disorder that pertains to the Frontotemporal Lobar Degeneration clinical syndromes. There is currently no approved pharmacological therapy for all frontotemporal dementia variants. Transcranial Direct Current Stimulation (tDCS) is a promising non-invasive brain stimulation technique capable of modulating cortical excitability through a sub-threshold shift in neuronal resting potential. This technique has previously been applied as adjunct treatment in Alzheimer’s disease, while data for frontotemporal dementia are controversial. In this scoped review, we summarize and critically appraise the currently available evidence regarding the use of tDCS for improving performance in naming and/or matching tasks in patients with svPPA. Clinical trials addressing this topic were identified through MEDLINE (accessed by PubMed) and Web of Science, as of November 2022, week 3. Clinical trials have been unable to show a significant benefit of tDCS in enhancing semantic performance in svPPA patients. The heterogeneity of the studies available in the literature might be a possible explanation. Nevertheless, the results of these studies are promising and may offer valuable insights into methodological differences and overlaps, raising interest among researchers in identifying new non-pharmacological strategies for treating svPPA patients. Further studies are therefore warranted to investigate the potential therapeutic role of tDCS in svPPA.